The Chronic Exercise-Cognition Interaction and Dementia and Alzheimer's Disease - de Melo Coelho, Flávia Gomes [UNESP]; Vital, Thays Martins [UNESP]; Santos-Galduróz, Ruth Ferreira [UNESP]; Gobbi, Sebastião [UNESP] (My University, 2015)
Research into the interaction between physical exercise and cognitive function in individuals with dementia has shown positive results. Studies demonstrate that patients with dementia in general or with Alzheimer's disease (AD), who are engaged in a program of physical exercise, may improve their cognition or reduce cognitive decline. Protocols of physical exercise that are most used by this population were multimodal or aerobic. For the elderly with AD, multimodal exercise seems to produce a better effect on cognitive functions. For the elderly with dementia, there is insufficient evidence to determine the best type of physical exercise. Potential mechanisms responsible for the benefits between regular physical exercise and mental health seem to result from physiological, biochemical, and psychosocial factors complexly interrelated. Thus, the nonpharmacological treatment of dementia and AD can be executed by means of physical exercise, in addition to pharmacological interventions.
Keywords: Alzheimer; Cognitive functions; Dementia; Neurobiological mechanisms; Nonpharmacological intervention; Physical exercise